Model of Social Capital Implementation in the Orphan Scholarship Program and Pick Up Outstanding Duafa in the Village: Case Study in Klangen Village, Klangen District, Cirebon Regency - Rochmat Hidayat (ann4publisher@gmail.com, 2026)
Background. The gap in access to education in rural areas is still a challenge for social development in Indonesia. Orphans from underprivileged families face the risk of dropping out of school due to limited education costs. In this context, local initiatives in the form of village scholarship programs are an important instrument to expand access to education based on social solidarity. Purpose. This study analyzes the management of social capital in the implementation of the orphan scholarship program in Klangen Village, Klangen District, Cirebon Regency. Method, This study uses a qualitative approach with a case study design, based on village program documentation and a synthesis of social capital literature. The theoretical framework refers to the perspectives of Putnam (bonding and bridging social capital), Bourdieu (social capital as a relational resource), and Coleman (the function of social capital in the creation of human capital). Results. The results of the analysis show that social capital bonding plays a strong role in the legitimacy and mobilization of local resources, while social capital bridging still needs to be strengthened to ensure the sustainability of the program. Conclusion. Strengthening formal governance and accountability mechanisms are key factors in maintaining public trust and program effectiveness. Implementation. This study recommends the integration of social capital with a transparent administrative system to improve the long-term impact of education.